1977
DOI: 10.1002/eji.1830070811
|View full text |Cite
|
Sign up to set email alerts
|

The role of the Fc receptor (FcR) of thymus‐derived lymphocytes II. Presence of FcR on suppressor cells and direct involvement in suppression

Abstract: The role of the Fc receptor (FcR) of thymus-derived I y m phocytes Presence of FcR on suppressor cells and direct involvement in suppression*Alloantigen-activated T cells (ATC) were prepared by injecting C3H/He thymocytes into host-irradiated BALB/c mice. ATC were taken from the spleen of the recipients at day 5 and tested for their activity o n "in vitro" primary antibody production t o sheep red blood cells (SRBC) induced in splenic C3H/He lymphocytes. ATC added 24 h after antigen were found t o be suppressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1979
1979
1984
1984

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In mice as well as in man it has been shown that T-cells release FcyR which exert nonspecific suppression of the primary PFC response to SE in vitro (19,20). The cells were found to be less suppressive after having lost their FcR (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mice as well as in man it has been shown that T-cells release FcyR which exert nonspecific suppression of the primary PFC response to SE in vitro (19,20). The cells were found to be less suppressive after having lost their FcR (19).…”
Section: Discussionmentioning
confidence: 99%
“…In mice as well as in man it has been shown that T-cells release FcyR which exert nonspecific suppression of the primary PFC response to SE in vitro (19,20). The cells were found to be less suppressive after having lost their FcR (19). Cordier et al (21) reported that the FcyR is irreversibly lost by human T-cells after interaction with insoluble immune complexes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that FcyR released by (activated) T cells suppress nonspecifically a primary PFC response to SE in vitro (Fridman et al 1977, Molenaar et al 1977. The finding that antigen-20 RUDY E. BALLIEUX' \ COBI J. HEIJNHN'.…”
Section: Identification Of Human T Suppressor Lymphocytesmentioning
confidence: 99%
“…IBF is produced by cortisone-resistant thymocytes [25] and by GVH-activated spleen T cells [25]. Whithin this cell population, IBF is produced by Fc receptor (FcR)-positive T cells [26], which themselves act as nonantigen-specific suppressors of in vitro antibody production [27]. IBF may, therefore, be the soluble form of the T cell FcR and the mediator of the suppression exerted by the FcR-positive activated T cells.…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis is strengthened by the fact that (a) IBF is only produced by FcR-positive T cells or FcR-positive T cell lines both in the mouse [26,281 and in man [29, 301; (b) IBF is produced at 37 "C in conditions where FcR is released from the T cell surface [26]. Incubation in the cold or in the presence of protein synthesis inhibitors, which blocks FcR release, inhibits IBF production [26]; (c) finally, activated T cells partially loose their suppressive activity after releasing their FcR, and this activity is found to be associated to IBF in the supernatant [27].…”
Section: Introductionmentioning
confidence: 99%